KINERJA KEUANGAN PEMERINTAH PROVINSI SUMATERA SELATAN TAHUN ANGGARAN 2015-2019 - Kusumadewi, Veronika Perwita (Balance : Jurnal Akuntansi dan Bisnis, 2021)
This study aims to evaluate the financial performance of the regional government of South Sumatra province over a period of five years (2015-2019). Financial ratio analysis is carried out to assess the financial performance of the regional government of South Sumatra Province. This research uses descriptive quantitative method. Research data in the form of secondary data, namely the Regional Government Financial Report of South Sumatra Province in 2015-2019. The research data was then analyzed using analysis of regional financial ratios, namely independence ratio, effectiveness ratio, efficiency ratio, growth ratio and harmony ratio. The results showed that the financial performance of the Government of South Sumatra Province is quite good but not optimal. Although the level of regional independence of the Government of South Sumatra Province is quite high, but the management of Regional Native Income (PAD) has not been effective and efficient enough. Analysis of ratio to PAD of South Sumatra Province shows that it has not entirely met the criteria effectively and efficiently. Revenue and spending growth in South Sumatra Province is still volatile from year to year. The calculation of the harmony ratio also shows operating expenditures dominate the allocation of regional spending instead of capital expenditures